PEMBELAJARAN BAHASA INGGRIS ANAK BERKEBUTUHAN KHUSUS DENGAN MENGGUNAKAN PERMAINAN BINGO DI YAYASAN SLB MARKUS MEDAN - Karisma Erikson Tarigan; Fiber Yun Almanda Ginting; Caecilia Adinda Rosa Sitohang (Yayasan Education and Social Center, 2021)
English learning activities for school-age children could not be separated by game methods that made a child learned to explore, discovered, expressed feelings, be creative, increased the activity of new thinking patterns, and provided opportunities to socialize with their environment. One example of a game that was starting to develop and be used in all areas of English language skills was bingo. The purpose of this community service was to describe the ability to improve the English language of special school students at the Markus Foundation through bingo games and as a guide for the implementation of English learning. The method used was the training in the use of vocabulary and speaking English through cards and powerpoint. The result of this community service activity was that the students were able to increase their English vocabulary through the bingo game because the researcher provided pictures and asked them to talk about the activities in the pictures. Bingo card pictures were able to provide clues to introduce the use of words and students practice a lot of pronunciation techniques with other students which made learning activities more challenging, motivated, and increased self-confidence. The existence of this training activity was expected to be able to develop the use of English as a foreign language in the context of the learning model of children with special needs in the form of interesting games and it required the responses of other students as a stimulation of the development of affective, cognitive, and psychomotor intelligence